Malicious URL Detection with Distributed Representation and Deep Learning - Do N.Q.; Selamat A.; Lim K.C.; Krejcar O. (IOS Press BV, 2023)
Computer crime; Convolutional neural networks; Embeddings; Natural language processing systems; Recurrent neural networks; Character level; Convolutional neural network; Deep learning; Distributed representation; Embeddings; Learning models; Malicious URL; Natural languages; Phishing detections; Word level; Websites